2007
DOI: 10.1073/pnas.0611202104
|View full text |Cite
|
Sign up to set email alerts
|

Activated vitamin D attenuates left ventricular abnormalities induced by dietary sodium in Dahl salt-sensitive animals

Abstract: Observations in hemodialysis patients suggest a survival advantage associated with activated vitamin D therapy. Left ventricular (LV) structural and functional abnormalities are strongly linked with hemodialysis mortality. Here, we investigated whether paricalcitol (PC, 19-nor-1,25(OH)2D2), an activated vitamin D compound, attenuates the development of LV abnormalities in the Dahl salt-sensitive (DSS) rat and whether humans demonstrate comparable findings. Compared with DSS rats fed a high-salt (HS) diet (6% N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
253
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(280 citation statements)
references
References 42 publications
21
253
2
4
Order By: Relevance
“…In that study, however, myocardial contractility parameters did not significantly change. Furthermore, treatment of 15 hemodialysis patients with an active vitamin D compound (paracalcitol) for 12 months was associated with an improvement in diastolic function and a reduction of septal and posterior wall thickness, whereas there was no effect on left ventricular ejection fraction [71].…”
Section: Active Vitamin D Treatment and Myocardial Functionmentioning
confidence: 98%
See 2 more Smart Citations
“…In that study, however, myocardial contractility parameters did not significantly change. Furthermore, treatment of 15 hemodialysis patients with an active vitamin D compound (paracalcitol) for 12 months was associated with an improvement in diastolic function and a reduction of septal and posterior wall thickness, whereas there was no effect on left ventricular ejection fraction [71].…”
Section: Active Vitamin D Treatment and Myocardial Functionmentioning
confidence: 98%
“…Apart from this, the noradrenergic chronotropic response of rat atria was significantly reduced by a vitamin D depleted diet [68]. Some animal studies have already evaluated the effect of active vitamin D treatment on myocardial structure and function [69][70][71][72]. In uremic rats, treatment with the active vitamin D analog paricalcitol protected against cardiac oxidative injury [70].…”
Section: Vitamin D-deficient Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with active vitamin D has been considered a key therapy for cardiovascular events in CKD,8 but controversy remains as beneficial effects on cardiac abnormalities as observed in animal models9 could not be confirmed in clinical trials 10, 11. Moreover, while in vitro studies suggested a protective role for vitamin D in ameliorating damaged endothelium,12, 13 experimental in vivo CKD studies have primarily focused on the prevention of vascular calcification of the medial layer and heart failure9, 14, 15 but paid little attention to structural endothelial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while in vitro studies suggested a protective role for vitamin D in ameliorating damaged endothelium,12, 13 experimental in vivo CKD studies have primarily focused on the prevention of vascular calcification of the medial layer and heart failure9, 14, 15 but paid little attention to structural endothelial damage. A small number of prior studies have suggested benefits of the active vitamin D analogue paricalcitol on endothelial stability in animal models of CKD16, 17 and even in patients 18, 19.…”
Section: Introductionmentioning
confidence: 99%